Clinical efficacy of fulvestrant versus exemestane as first-line therapies for Chinese postmenopausal oestrogen-receptor positive /human epidermal growth factor receptor 2 -advanced breast cancer (FRIEND study). (May 2023) - Wang, Jiayu; Cai, Li; Song, Yanqiu; Sun, Tao; Tong, Zhongsheng; Teng, Yuee; Li, Huiping; Ouyang, Quchang; Chen, Qianjun; Cui, Shude; Yin, Yongmei; Liao, Ning; et al.
Abstract: Aim: To compare the efficacies of exemestane and fulvestrant as first-line monotherapies for postmenopausal Chinese women having advanced oestrogen-receptor positive (ER+)/ human epidermal growth factor receptor 2 (HER2)-breast cancer (ER+/HER2- ABC) after a previous treatment for ≥2 years with an adjuvant non-steroidal aromatase inhibitor. Methods: In this randomised, open-label, multi-centre, parallel-controlled phase 2 FRIEND study, 145 postmenopausal ER+/HER2- ABC patients were assigned into fulvestrant (500 mg on days 0, 14 and 28, and then at every 28 ± 3 days, n = 77) and exemestane (25 mg/day, n = 67) groups. The primary outcome was progression-free survival (PFS), while the secondary outcomes were disease control rate, objective response rate, time to treatment failure, duration of response and overall survival. Exploratory end-points included gene mutation-related outcomes and safety. Results: Fulvestrant was superior to exemestane regarding median PFS times (8.5 versus 5.6 months, p = 0.014, HR = 0.62, 95% confidence intervals: 0.42–0.91), objective response rates (19.5% versus 6.0%, p = 0.017) and time to treatment failure (8.4 versus 5.5 months, p = 0.008). The incidence of adverse or serious adverse events in the two groups was virtually identical. The most frequent mutations in 129 analysed patients were detected in the o estrogen receptor gene 1 ( ESR1 ) (18/14.0%), PIK3CA (40/31.0%) and TP53 (29/22.5%) genes. Fulvestrant produced significant longer PFS times compared to exemestane but only for patients with an ESR1 -wild type (8.5 versus 5.8 months) ( p = 0.035), although there was a similar trend also for the ESR1 mutation without statistical significance. All patients with c-MYC and BRCA2 mutations had longer PFS times in the fulvestrant versus the exemestane group ( p = 0.049, p = 0.039). Conclusion: Fulvestrant significantly increased overall PFS for ER+/HER2- ABC patients and was well tolerated. ClinicalTrials: NCT02646735, https://clinicaltrials.gov/ct2/show/NCT02646735 . Highlights: The novel selective oestrogen receptor down regulator fulvestrant is administered to hormone receptor positive advanced breast cancer patients. Exemestane, a steroidal aromatase inhibitors, is used to treat early and advanced breast cancer patients. Fulvestrant was superior to exemestane regarding median progression-free survival times and time to treatment failure. c-MYC and BRCA2 mutations led to longer progression-free survival times in the fulvestrant group.